Exploration of Leisure Time Valuation to Explain Sex-Based Wage Gaps among Salaried Primary Care Physicians in the US - Weeks, William B.; Ventelou, Bruno (Journal of Reviews on Global Economics, 2017)
In the US, female physicians have lower hourly incomes than their male counterparts, across specialties and after adjusting for physician and practice characteristics; however, female physicians work fewer hours than their male counterparts. We wanted to determine whether a simple method of valuing leisure time - overtime pay - might help explain sex-based wage gaps among US primary care physicians. Therefore, we used Community Tracking Study Physician Survey data from 1996-2005 to model the impact of overtime pay on sex-based wage gaps. As overtime premiums increased in our models, sex-based wage disparities decreased: they become statistically insignificant when overtime wages reached 0%, 32%, and 61% premiums using the ordinary least squared model and with 0%, 62%, and 55% premiums using the propensity score weighted model, for internal medicine, family practice, and pediatric physicians, respectively. We conclude that modest overtime premiums reduced sex-based hourly wage gaps for the salaried primary care physicians we examined. Future analyses of sex-based wage gaps should account for leisure time and its trade for work hours when it becomes scarce.